Effect of phosphorus and zinc fertilization on productivity and nutrient uptake of mothbean - Puniya, M.M.; Shivran, A.C.; Khangarot, S.S.; Kuri, B.R.; Choudhary, S.P. (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif season of 2010 on loamy sand soil to study the effect of phosphorus levels and zinc application on profitability, nutrient content and uptake of mothbean. Experiment consisted of four treatments of phosphorus levels (0, 20, 40 and 60 kg P2O5/ ha) and four treatments of zinc application (control, soil application @ 5 kg Zn/ha, soil application + one foliar spray @ 0.5% Zn at 25 DAS and soil application + two foliar spray @ 0.5% Zn at 25 and 40 DAS) thereby making sixteen treatment combinations tested in randomized block design with three replications. Results indicated that application of phosphorus up to 40 kg/P2O5 significantly increased seed and straw yields, net returns, protein content in seed, phosphorus and zinc content in seed and straw and total uptake of nitrogen, phosphorus and zinc over preceding levels and remained at par with 60 kg P2O5/ha. Whereas, application of 60 kg P2O5/ha significantly increased the nitrogen content in seed and straw and did not have any significant effect on harvest index. Combined soil application of zinc @ 5 kg/ha + one foliar spray of zinc @ 0.5% significantly increased the seed and straw yields, net returns, protein content, nitrogen, phosphorus and zinc content in seed and straw and total uptake of nitrogen, phosphorus and zinc over control and it remained at par with soil application of zinc @ 5 kg ha-1.